Find the sum of all positive integers such that has a terminating decimal representation.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
First, note that a fraction k m with coprime positive integers m and k has a terminating decimal representation if and only if k = 2 a 5 b . Otherwise, there would exist no c , such that k m ⋅ 1 0 c is an integer.
Then, rewrite N = n ( n − 1 ) 2 n + 1 = n ( n − 1 ) 2 n + ( n − n ) + 1 = n − 1 3 − n 1 . Both n − 1 3 and n 1 have to terminate in order for N to be terminating. If n would have a factor that is not a multiple of 2 or 5 , then the second term would not terminate. If n would be a multiple of 2 and 5 , n − 1 would be coprime to 2 and 5 and the first term would not terminate. Thus n = 2 k or 5 k such that (for some l ) either 2 k − 1 = 5 l , 5 k − 1 = 2 l , 2 k − 1 = 3 ⋅ 5 l o r 5 k − 1 = 3 ⋅ 2 l .
Case 1: n = 2 k and n − 1 = 5 l ⇔ 2 k = 5 l + 1 . Since 5 l + 1 ≡ 1 l + 1 ≡ 2 ( m o d 4 ) , the only solution to this equation is k = 1 , l = 0 and therefore n = 2 .
Case 2: n = 5 k and n − 1 = 2 l . Assume k = 2 b . Then 2 l = 5 2 b − 1 = ( 5 b − 1 ) ( 5 b + 1 ) . We have already shown that 5 b + 1 = 2 m can only hold true for b = 0 . Now assume k = 2 b − 1 . Note that ∑ i = 0 d a i = a − 1 a d + 1 − 1 . Using this, consider 2 l = 5 2 b − 1 − 1 = 4 ( i = 0 ∑ 2 b − 2 5 i ) . This only holds true if both factors are a power of 2 . Since the sum is always odd, the only possible value for the second factor is 1 and thus b = k = 1 and therefore n = 5 .
Case 3: n = 2 k and n − 1 = 3 ⋅ 5 l . Note that, for l > 0 , this expression's last digit is 5 . Therefore k = 4 b and 3 ⋅ 5 l = 2 4 b − 1 = ( 2 2 b − 1 ) ( 2 2 b + 1 ) , which we have shown in case 1 and case 2 to only be true for b = 1 , k = 4 and therefore n = 1 6 . For l = 0 we find 2 2 − 1 = 3 ⋅ 5 0 and n = 4
Case 4: n = 5 k and n − 1 = 3 ⋅ 2 l . This can be proven almost identically to case 2. It yields k = 2 and therefore n = 2 5 .
Summing all of them together makes 2 + 4 + 5 + 1 6 + 2 5 = 5 2 .
Note: These are special cases of Catalan's conjecture .